2014
DOI: 10.1371/journal.pcbi.1003560
|View full text |Cite
|
Sign up to set email alerts
|

Spike-Threshold Adaptation Predicted by Membrane Potential Dynamics In Vivo

Abstract: Neurons encode information in sequences of spikes, which are triggered when their membrane potential crosses a threshold. In vivo, the spiking threshold displays large variability suggesting that threshold dynamics have a profound influence on how the combined input of a neuron is encoded in the spiking. Threshold variability could be explained by adaptation to the membrane potential. However, it could also be the case that most threshold variability reflects noise and processes other than threshold adaptation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
150
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(160 citation statements)
references
References 55 publications
10
150
0
Order By: Relevance
“…We provided an explanation how bandpass filtering can emerge via threshold. Even though we cannot be conclusive about the origin of threshold adaptation, whether sodium (Fontaine et al 2014;Hu et al 2009;Kuba et al 2010) or potassium (Goldberg et al 2008;Higgs and Spain 2011) channel dynamics underlie the phenomenon, we showed that a model representing sodium channels with appropriate biophysical inactivation properties can explain the data. Indeed, the shape of the threshold steady-state function was crucial in explaining the dependence of the filtering on input level.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…We provided an explanation how bandpass filtering can emerge via threshold. Even though we cannot be conclusive about the origin of threshold adaptation, whether sodium (Fontaine et al 2014;Hu et al 2009;Kuba et al 2010) or potassium (Goldberg et al 2008;Higgs and Spain 2011) channel dynamics underlie the phenomenon, we showed that a model representing sodium channels with appropriate biophysical inactivation properties can explain the data. Indeed, the shape of the threshold steady-state function was crucial in explaining the dependence of the filtering on input level.…”
Section: Discussionmentioning
confidence: 60%
“…The threshold (t) has a spike-triggered adaptive process (Benda et al 2010;Chacron et al 2007;Platkiewicz and Brette 2010), i.e., (t) increases by a fixed amount ␣ every time a spike is fired, i.e., (t) ¡ (t) ϩ ␣. The subthreshold dynamics of the threshold (t) is governed by the first-order differential equation with a steady-state function that depends on V m (t) (Farries et al 2010;Fontaine et al 2014;Higgs and Spain 2011;Platkiewicz and Brette 2010):…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations